Production of Ibuprofen Pellets Containing High Amount of Rate Retarding Eudragit RL Using PEG400 and Investigation of Their Physicomechanical Properties - Sadeghi, Fatemeh (Mashhad University of Medical Sciences, 2011)
OBJECTIVE(S): The aim of this study was to investigate the possibility of production of ibuprofen pellets with high amount of rate retarding polymer by aid of PEG400 as plasticizer. MATERIALS AND METHODS: Polyethylene glycol (PEG400) in concentrations of 1, 3 or 5% w/w with respect to Eudragit RL was used in production of pellets containing 60% ibuprofen and 40% excipient (2% polyvinylpyrrolidone (PVP), 7.6 or 0% microcrystalline cellulose (MCC) and 30.4 or 38% Eudragit RL). Physicomechanical and release properties of pellets were evaluated. RESULTS: In presence of PEG400, formulations containing 30.4% Eudragit RL and 7.6% MCC could easily form pellets. In formulations without any MCC pellets were obtained only in presence of 3 or 5% PEG400. Pellets containing MCC with 0 or 1% PEG400 showed brittle properties but those with 3% or 5% PEG400 showed plastic nature under pressure. Elastic modulus dramatically decreased with increasing PEG400 indicating softening of pellets. This was due to shift of Eudragit structure from glassy to rubbery state which was supported by DSC studies. Mean dissolution time (MDT) increased with addition of 1 or 3% PEG400 but this was not the case for pellets with 5% PEG400. CONCLUSION: Overall PEG400 is a potential plasticizer in production of pellets based on Eudragit RL and ibuprofen. The ease in process of extrusion-spheronization, increasing the mean dissolution time and change in mechanical properties of pellets from brittle to plastic behavior were advantages of using PEG400. Changes in mechanical properties of pellets are important when pellets are intended to be compressed as tablets.